Toward More People-Centered Service Delivery : Opportunities for the National ID System in Lesotho - World Bank (Washington, DC, 2022)
This note documents the current and emerging use cases for the national ID (NID) system in the Kingdom of Lesotho. It demonstrates considerable potential and progress to date, and makes recommendations for moving toward a more inclusive, trusted and service delivery-oriented NID system. Global experience has shown that national ID systems can promote more efficient, transparent and people-centered service delivery in the public and private sectors, particularly when the system is designed with the appropriate enablers and safeguards in place to support improved development outcomes and mitigate risks. As countries move toward digital economies and governance, ID systems often serve as an essential digital platform, underpinning the digital payment infrastructure and transactions, as well as the provision of online and offline government services.